Work and leisure - Haworth, John T. (John Trevor), 1937-; Haworth, John Trevor; Veal, Anthony James (London ; New York : Routledge, 2004)
"Work and Leisure brings together specially commissioned chapters from international experts in a wide range of disciplines concerned with work, leisure and well-being. Each author takes stock of the current position, identifies core practical and theoretical issues and discusses possible future trends in order to provide an invaluable resource for all policy-makers, educators, employers and researchers in the field."--BOOK JACKET.
A brief history of work and its relationship to leisure / A.J. Veal -- The devil still makes work / Chas Critcher and Peter Bramham -- Postmodern work and leisure / Chris Rojek -- Gender, work and leisure / Judy White -- The economics of work and leisure / Chris Gratton and Peter Taylor -- Looking back : perspectives on the leisure-work relationship / A.J. Veal -- Work, leisure, time-pressure and stress / Jiri Zuzanek -- Stress and working parents / Barbara Scheneider, Alisa Ainbinder, and Mihalyi Csikszentmihalyi -- Work, leisure and wellbeing / John Haworth -- Leisure and health / Seppo Iso-Ahola and Roger Mannell -- Serious leisure, volunteerism and quality of life / Robert Stebbins -- Work and leisure : themes and issues / John Haworth and A.J. Veal.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Well-being.; Work; Leisure; Voluntarism; Well-being.; Quality of life; Twenty-first century -- Forecasts; Electronic books